Guest editors’ introduction: “west-east” lyric: a comparative approach to lyric history - Burney, Fatima; Grewal, Sara (My University, 2020)
For comparatists, the question of how to compare, or what constitutes the grounds of comparison, has defined the field since its inception; comparison as method seems to provoke a turn toward the self-reflexive for its practitioners, perhaps in an attempt to avoid the age-old problem of apples and oranges. This concern becomes further pronounced for those of us who work between traditions construed broadly as either 'Eastern' or 'Western', since the sense of shared roots in literary cultures either fades substantially, or provides painful reminders of the stark contrasts in power differentials between the two in the context of Western colonialism and its enduring effects since at least the sixteenth century. How, then, to compare? This question becomes marked once again for those of us who focus on poetry, which has been dominated by the discourse around a 'lyrical ideal" that eschews the 'real world' of politics and social realities in favour of a focus on the self, as well as on a particular 'lyric I' which functions as the site of an unproblematically universal vision of selfhood.
Keywords: lyric history; poetry